Third Five Year Plan Punjab State Part I - Planning Commission (Planning Commission, 1960)
Punjab’s Third Plan. as presented in these documents, is essentially a "programme" plan. That is to say it consists of a practical five-year programme of work for the various departments. The programme has been drawn up as a result of months of careful thinking. The main features that have been kept in mind are the national targets and points of national policy set out in the Draft Outline, the special circumstances and needs of this Stale, the level of development and the pace of implementation attained in the Second Plan and the likely executing capacity of the departments in the next five years. Briefly, it is felt needs and executing capacity that have largely determined the size and shape of this plan.
Planning Department, Punjab